BOOK REVIEW: AFTER THE EXODUS: Gender and Belonging in Bangladesh’s Rohingya Refugee Camps - Rahman, Farhana (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
After the Exodus examines how forced migration of the Rohingya from Myanmar to Bangladesh has affected the gendered subjectivities and lived experiences of Rohingya refugee women, and transformed gender relations and roles in displacement. Based on 14 months of feminist ethnographic fieldwork in Bangladesh’s KutupalongBalukhali refugee camp in 2017 and 2018, the book uncovers the everyday strategies employed by refugee women to create a sense of belonging and to make a life for themselves after forced migration. Rohingya women adapt to camp life by negotiating marriage and intimate experiences, adjusting to changing gender divisions of labour, and navigating encounters with humanitarian aid agencies and male camp leaders. These women strategically bargain shifting power relations to reconstruct their lives in displacement, thereby reclaiming agency and asserting their identity through the spaces they create, inhabit, and reshape; the coping mechanisms they employ; and the bonds of kinship and community they forge.Farhana Afrin Rahman is currently a Leverhulme Early Career Fellow and Isaac Newton Trust Fellow at the Department of Politicsand International Studies, University of Cambridge, and a Junior Research Fellow at Wolfson College, Cambridge. Her research interests include gender, refugees and forced migration, international development, lived experiences, and violence and conflict, amongst others